Peningkatan Pemahaman Konsep Peluang Kejadian Majemuk Melalui Model Pembelajaran Discovery Learning Berbantuan Alat Peraga Dadu - Warti, Yusnimi (Minangkabau Scholar Institute, 2020)
This study aims to describe the understanding of the concept of multiple event opportunities through the Discovery Learning model assisted by the dice props in class XII at SMA N 1 Ampek Angkek, Agam Regency, West Sumatra. This research is a collaborative classroom action research where researchers are teachers and friends who collaborate in conducting research. The subjects of this study were students of class XII MIPA 5 of SMAN 1 Ampek Angkek, Agam Regency, West Sumatra, TP 2019/2020 in the even semester. Data collection techniques using observation, tests, field notes, and documentation. Data analysis techniques use data reduction, data presentation, and verification or conclusion drawing, while the validity of the data uses triangulation techniques. This study uses two cycles, where each cycle consists of two meetings. The results of this study indicate an increase in understanding the concept of multiple event opportunities by using the Discovery Learning model assisted by dice props.